Mixed Reality Application for Virtual Tourism: Annah Rais Longhouse - Muhammad Khairul Bin Anthony Hasbi; Liew, Lee Hung; Abdul Hadi Bin Abdul Talip; Firdaus Abdullah; Howe Eng Tang; Beng Yong Lee; Heng Yen Khong; Ranee Atlas; Patricia Melvin Jussem, (ECTI Transactions on Computer and Information Technology (ECTI-CIT), 2025)
The tourism industry worldwide has faced unprecedented challenges recently, which has increased the need for innovative solutions to showcase destinations sustainably. Virtual tourism has emerged as a transformative response to these challenges, allowing individuals to explore destinations remotely through immersive digital experiences. Malaysia is renowned for its breathtaking natural landscapes and diverse cultural heritage, such as the Annah Rais Longhouse in Sarawak. Despite the decline in tourist numbers, there are concerns about the degradation of Sarawak's natural sites. Furthermore, individuals with disabilities often encounter barriers when trying to access these locations, which can exacerbate feelings of exclusion and isolation. This research focuses on developing a mixed reality (MR) application that leverages immersive technology to provide virtual tourism experiences, preserve natural attractions, and enhance accessibility for all types of visitors in response to these issues. The research adopted the multimedia development life cycle encompassing ve key stages: concept, design, data gathering, assembly, and testing. The developed MR applica- tion offers users two modes: Explore Mode and Virtual Tour Mode. With the integration of interactive elements, the MR application allows users to delve deeper into the history and significance of the cultural heritage, which positively contributes to the tourism industry in Sarawak. The developed MR application was evaluated using the constructs of perceived ease of use (PEOU), perceived usefulness (PU), perceived interaction (PI), and telepresence (TP). Descriptive analyses of the constructs were conducted. The results demonstrated that the MR application is well-accepted.